2019
DOI: 10.1017/s1474745618000496
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Binding Commitments on Services Trade

Abstract: It has long been established in theory that uncertainty impacts on firm behaviour. However, the empirical basis for quantifying the uncertainty-reducing effects of trade agreements has not been firmly established. In this paper, we develop estimates of the effect of reducing uncertainty regarding regulation of foreign services markets by making commitments that are bound under a trade agreement. Specifically, we identify the effect on services trade of services trade restrictions, as measured by the OECD's Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Not controlling for such accessibility issues provides biased outcomes no matter how good specification has been chosen for the analysis. Controlling for multilateral trade resistance can be done by various methods; however, we primarily apply the technique used by Dall'Erba et al (2021), Ciuriak et al (2020) and Feenstra (2016). The approach these studies is known as the pairwise time-FE.…”
Section: Robustness Of the Resultsmentioning
confidence: 99%
“…Not controlling for such accessibility issues provides biased outcomes no matter how good specification has been chosen for the analysis. Controlling for multilateral trade resistance can be done by various methods; however, we primarily apply the technique used by Dall'Erba et al (2021), Ciuriak et al (2020) and Feenstra (2016). The approach these studies is known as the pairwise time-FE.…”
Section: Robustness Of the Resultsmentioning
confidence: 99%
“…commitments in trade agreements often is considerable (see, e.g., Borchert, Gootiiz, and Mattoo, 2011;Miroudot and Shepherd, 2014;Miroudot and Pertel, 2015;Ciuriak et al, 2017). Research on the value of reducing the difference between bound and applied services policies has shown that this may be an important source of welfare gain, driven by a reduction in policy uncertainty (Lamprecht and Miroudot, 2018;Ciuriak et al, 2019;Egger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There is no "water" for measures that are not covered by GATS commitments (Figure 1). 5 Another feature of the GATS is that countries are free to make commitments or not in any sector or subsector. However, when they do not have market access or national treatment commitments in a specific sector or sub-sector, they still create "water".…”
Section: Methodsmentioning
confidence: 99%
“…The intra-EEA STRI, on the other hand, is an example of an application of the STRI to quantify preferential regimes. The intra-EEA STRI measures barriers to services trade in the Single Market of the European Economic Area, where the internal regulatory environment for services trade is much more liberal than that which is applied towards third countries (Benz and Gonzales, 2019 [5]).…”
Section: Introductionmentioning
confidence: 99%